Recurrent hemorrhage risk and mortality in hereditary and sporadic cerebral amyloid angiopathy. (4th October 2016) - van Etten, Ellis S.; Gurol, M. Edip; van der Grond, Jeroen; Haan, Joost; Viswanathan, Anand; Schwab, Kristin M.; Ayres, Alison M.; Algra, Ale; Rosand, Jonathan; van Buchem, Mark A.; Terwindt, Gisela M.; Greenberg, Steven M.; et al.
Abstract : Objective: To determine whether hereditary cerebral hemorrhage with amyloidosis–Dutch type (HCHWA-D), a monogenetic disease model for the sporadic variant of amyloid angiopathy (sCAA), has a comparable recurrent intracerebral hemorrhage (ICH) risk and mortality after a first symptomatic ICH. Methods: We included patients with HCHWA-D from the Leiden University Medical Center and patients with sCAA from the Massachusetts General Hospital in a cohort study. Baseline characteristics, hemorrhage recurrence, and short- and long-term mortality were compared. Hazard ratios (HRs) adjusted for age and sex were calculated with Cox regression analyses. Results: We included 58 patients with HCHWA-D and 316 patients with sCAA. Patients with HCHWA-D had fewer cardiovascular risk factors (≥1 risk factor 24% vs 70% in sCAA) and were younger at the time of presenting hemorrhage (mean age 54 vs 72 years in sCAA). Eight patients (14%) with HCHWA-D and 46 patients (15%) with sCAA died before 90 days. During a mean follow-up time of 5 ± 4 years (total 1, 550 person-years), the incidence rate of recurrent ICH in patients with HCHWA-D was 20.9 vs 8.9 per 100 person-years in sCAA. Patients with HCHWA-D had a long-term mortality of 8.2 vs 8.4 per 100 person-years in patients with sCAA. After adjustments, patients with HCHWA-D had a higher risk of recurrent ICH (HR 2.8; 95% confidence interval 1.6–4.9; p < 0.001) and a higher long-term mortality (HR 2.8; 95% confidence interval 1.5–5.2; p = 0.001). Conclusions: Patients with HCHWA-D have worse long-term prognosis after a first ICH than patients with sCAA. The absence of cardiovascular risk factors in most patients with HCHWA-D suggests that vascular amyloid is responsible for the recurrent hemorrhages. HCHWA-D is therefore a pure form of cerebral amyloid angiopathy with an accelerated clinical course and provides a good model to study the pathophysiology and future therapeutic interventions of amyloid-related hemorrhages.